Evaluating the Implementation of Artificial Intelligence in Recruitment and Employee Selection: A Case Study of Indomaret South Sulawesi - Surianti , Surianti (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to evaluate the implementation of Artificial Intelligence (AI) in recruitment and employee selection at Indomaret South Sulawesi. The research adopts a quantitative approach with a case study design, involving respondents from human resource personnel and employees engaged in recruitment processes. Data were collected through structured questionnaires using a Likert scale and analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that AI implementation has a significant positive effect on recruitment efficiency and selection quality. AI systems contribute to faster hiring processes, improved data processing, and more accurate candidate-job matching. However, the study also finds that AI implementation is accompanied by several challenges, including technological limitations, lack of user competence, and resistance to change. These challenges have a significant negative effect on selection quality, indicating that the success of AI adoption is highly dependent on organizational readiness. This study concludes that AI has strong potential to enhance recruitment performance in the retail sector, particularly in high-demand environments such as Indomaret. Nevertheless, its effectiveness requires a balance between technological advancement and human resource capability. The findings contribute to the development of AI-based human resource management practices and provide practical insights for organizations seeking to optimize recruitment processes through digital transformation